Living heritage conservation: from commodity-oriented renewal to cultureoriented and people-centred revival - Xu, Yiran (International Planning History Society Proceedings, 2018)
Living Heritage is characterized by ‘continuity’, in particular those historic places that are still a ‘living’ part of their community. In China, the mainstream of living heritage conservation is shifting from commodity-oriented renewal to culture-oriented and people-centred revival, which has obviously displayed in many planning practices. This paper centres on the connotation of living heritage and explores its applications approaches through two conservation practices in Nanjing, China. In the first project, the author conceived a brand-new way of protecting and revealing historic streets, named ‘Reflection Alley’. It treats the street as an open museum, utilizing current semi-dismantled remains, providing a stage for dialogues between history and modernity, endowing the historic legacy with a sustainable future. In the second project, a ‘Five-stakeholder Platform’ is set up to support the progressive revitalization of a historic district. Through in-depth community engagement, the design team have developed a three-phase planning guide helping locals to protect and repair their residences thus stimulating the vitality of community life. The paper provides solutions for the implementation of culture-oriented and people-centred revival through the interaction between tangible and intangible parts and the connections to community.